2019
DOI: 10.1111/josi.12365
|View full text |Cite
|
Sign up to set email alerts
|

Overestimating One's “Green” Behavior: Better‐Than‐Average Bias May Function to Reduce Perceived Personal Threat from Climate Change

Abstract: The actions of others, and what others approve of, can be a powerful tool for promoting proenvironmental behavior. A potential barrier to the utility of social norms, however, are cognitive biases in how people perceive themselves and others, including the better‐than‐average effect. This effect describes the tendency for people to think they are exceptional, especially when compared with their peers. To investigate the role of the better‐than‐average effect in proenvironmental behavior, we administered questi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 37 publications
1
20
0
Order By: Relevance
“…For example, exonerative comparisons can allow people to morally justify their own behaviour by assuming that they are at least better than many of their peers. Indeed, we have found elsewhere that people tend to perceive their own engagement in pro-environmental behaviour to be as good as, or better than, those of their peers (Leviston & Uren, 2020). This uniqueness bias may only partially excuse one's behaviour, however; cognitive reconstrual of the meaning and impacts of one's behaviour may be more effective.…”
Section: Mechanisms Of Moral Disengagementmentioning
confidence: 90%
“…For example, exonerative comparisons can allow people to morally justify their own behaviour by assuming that they are at least better than many of their peers. Indeed, we have found elsewhere that people tend to perceive their own engagement in pro-environmental behaviour to be as good as, or better than, those of their peers (Leviston & Uren, 2020). This uniqueness bias may only partially excuse one's behaviour, however; cognitive reconstrual of the meaning and impacts of one's behaviour may be more effective.…”
Section: Mechanisms Of Moral Disengagementmentioning
confidence: 90%
“…However, to our knowledge, there are a few studies on self-enhancement bias related to pro-environmental behaviors [56]. Bergquist [57] found that people perceive themselves as more pro-environmental than others in terms of conserving energy, recycling, and so on.…”
Section: Self-others Discrepanciesmentioning
confidence: 99%
“…Nevertheless, little direct evidence indicates whether self-enhancement bias exists for the domain of waste separation in the context of mandatory and voluntary policies. According to prior studies [56,57], we predicted that people assess themselves as more likely to sort waste than others in both mandatory and voluntary conditions and to hold a more positive attitude toward waste separation than others.…”
Section: Self-others Discrepanciesmentioning
confidence: 99%
“…Another feature of social life is social comparison and the importance of both descriptive and injunctive norms. Leviston and Uren (2020) focus on people's beliefs about their and others' pro-environmental behaviors. Few of their participants reported that they thought they did fewer pro-environmental behaviors than average-clear evidence of the well-known "better-than-average" effect (e.g., Brown, 2012).…”
Section: The Individual In the Centermentioning
confidence: 99%